The hamster revolution for meetings : how to meet less and get more done - Song, Mike, 1964- (BK business book., 2009)
"In this business fable, Iris--a meetings-inundated vice president--meets a coach who introduces her to a straightforward process that helps her eliminate unnecessary meetings, improve meeting quality, and save 15 days a year in previously wasted time."--Resource description page.